Ejaculatory abstinence duration impacts semen parameters: Insights from a retrospective analysis in male infertility on 23,527 analyses - Russo, Giorgio Ivan; Asmundo, Maria Giovanna; Cocci, Andrea; Abdelhameed, Ali Saber; Liprino, Annalisa; Giacone, Filippo; Lombardo, Debora; Guglielmino, Antonino; Chamayou, Sandrine (Frontiers in Endocrinology, 2025)
PurposeEjaculatory abstinence (EA) duration is recognized to impact semen parameters. This study aims to evaluate the effects of varying EA durations on semen quality parameters, distinguishing between normospermic and sub-fertile men, and to provide insights into tailored abstinence recommendations for improved fertility outcomes.MethodsWe retrospectively analyzed 23,527 semen samples from men undergoing infertility evaluation from 2013 to 2024. Semen parameters, including sperm concentration, motility, and morphology, were assessed post-abstinence (2–7 days) according to WHO guidelines. Group differences were analyzed, focusing on sperm parameters across abstinence periods in normospermic versus patients with sperm abnormalities.ResultsIn normospermic patients we found a trend increase from day 1 to day 7 of abstinence time regarding total sperm count (million) (92.4 vs. 191.1; p<0.01), sperm concentration (million/ml) (44.5 vs. 72.0; p<0.01) and morphology (6 vs. 12.5; p= 0.03) but not regarding motility (A+B) (50.0% vs. 48.0%; p=0.43). Conversely, in the population of patients with sperm abnormality, we found a significant trend increase from day 1 to day 7 of TSC (16.38 vs. 56.0; p<0.01), sperm concentration (million/ml) (8.0 vs. 18.0; p<0.01) and morphology (3.0 vs. 5.0; p<0.01). Interestingly, we found a significant trend decrease of motility (A+B) (28.0% vs. 21.0%; p<0.01) and pH (8.1 vs. 7.9; p<0.01) In patients affected by asthenospermia, motility (A+B) dropped significantly from day 1 to day 7 (11.8% vs. 6.1%; p<0.01) and also in patients with teratospermia morphology dropped significantly (2.13% vs. 1.26%; p<0.01).ConclusionThe findings support the use of tailored abstinence guidelines to optimize semen quality based on patient-specific semen profiles, with normospermic men benefiting from longer abstinence durations to increase concentrations, while patients with motility or morphology impairments, may benefit from shorter abstinence periods to mitigate sperm quality declines.